If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3(x-1)-(x+1)=0
We simplify the equation to the form, which is simple to understand
3(x-1)-(x+1)=0
Reorder the terms in parentheses
+(+3x-3)-(x+1)=0
Remove unnecessary parentheses
+3x-3-(+x+1+)=0
Remove unnecessary parentheses
+3x-3-1x-1=0
We move all terms containing x to the left and all other terms to the right.
+3x-1x=0+3+1
We simplify left and right side of the equation.
+2x=+4
We divide both sides of the equation by 2 to get x.
x=2
| x+(x-4)=42 | | x*x=124 | | m=-49.4=-10.9 | | 9x2-4=0 | | -7y+5(y+4)=18 | | -5n-8(1/2+7n)=-94 | | 3/4=k/2 | | 13/254=6/x | | 4r−3=3(3r+4) | | 8a-3=-5 | | 4-3x=8-5x | | 8.w=120 | | (1÷2)x+(3÷4)×(x-2)=(1÷3)×(2x-3) | | 23m=161 | | x+4/5=8/15 | | 8n-32=9-n | | 4m+7=–3m+49 | | 4/x+1+6/3x+1=15/3x+1 | | -10+7(8-6b)=-6(12b+9) | | 16=x+4+2(8-6) | | 0,804x=201 | | (3n+1)^2-25=0 | | 1/2m=7/2 | | |x-1|=0.01 | | 32x+8=32x+8 | | 2x+5=8x–4 | | x–(x–7)=3 | | 16−2t=2/3t+9 | | x+2.2=-8.1 | | 15(x−5)=16 | | 4m-7=8+2 | | 3w=5w=72 |